2014
DOI: 10.3174/ajnr.a3987
|View full text |Cite
|
Sign up to set email alerts
|

Interhypothalamic Adhesion: A Series of 13 Cases

Abstract: SUMMARY:Interhypothalamic adhesion is a newly described disease entity, characterized by an abnormal parenchymal band connecting the medial margins of the hypothalami across the third ventricle. Additional anomalies, including cleft palate, gray matter heterotopia, cerebellar hypoplasia, optic atrophy, hippocampal under-rotation, and white matter lesions, may coexist. The purpose of this clinical report is to describe the imaging findings from a series of 13 patients with interhypothalamic adhesions discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 10 publications
(12 reference statements)
1
14
0
Order By: Relevance
“…Hypothalamic adhesions have been firstly reported in patients with Chiari II malformation by Miller et al as bridges of tissue, isointense to gray matter on all sequences, connecting the hypothalamus across the anterior inferior portion of the third ventricle typically attached to the lower portion of the lamina terminalis [34]. Recently, Whitehead et al described similar parenchymal bands of tissue mainly extending to the tuber cinereum (called by these authors as Binterhypothalamic adhesions^) in 13 patients with different malformative features, ranging from mild hippocampal under-rotation to severe malformations of brain development [39]. Since midline anomalies were coexistent in most of these patients, the authors suggested that the interhypothalamic adhesions could be considered a type of form fruste holoprosencephaly.…”
Section: Type B Dmj Patternmentioning
confidence: 96%
“…Hypothalamic adhesions have been firstly reported in patients with Chiari II malformation by Miller et al as bridges of tissue, isointense to gray matter on all sequences, connecting the hypothalamus across the anterior inferior portion of the third ventricle typically attached to the lower portion of the lamina terminalis [34]. Recently, Whitehead et al described similar parenchymal bands of tissue mainly extending to the tuber cinereum (called by these authors as Binterhypothalamic adhesions^) in 13 patients with different malformative features, ranging from mild hippocampal under-rotation to severe malformations of brain development [39]. Since midline anomalies were coexistent in most of these patients, the authors suggested that the interhypothalamic adhesions could be considered a type of form fruste holoprosencephaly.…”
Section: Type B Dmj Patternmentioning
confidence: 96%
“…Only 2 reports in the literature describe this entity. 4,5 The first report in 2013 characterized a single patient presenting with IHA in association with a cleft palate deformity. 4 The second report in 2014 was a case series of 13 patients in which most IHAs were thought to be associated with other midline structural abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The band of tissue was measured on MR imaging and, as performed in a previously published smaller case series, the possible nuclei involved in the hypothalamic connection were inferred from the segmentation scheme devised by Lemaire et al 10 on the basis of anatomic landmarks. 5 Hypothalamic dysfunction was surmised from history and clinical symptoms. The patients' charts were reviewed by using the Epic electronic medical record system (Epic Systems, Madison, Wisconsin) at Children's Hospital Colorado for their medical history and symptomology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] These may be subtle and insignificant (hypoplasia of the falx, underrotated hippocampi, and so forth) or obvious and potentially of great consequence (malformations of brain development). [2][3][4] Indeed, review of Fig 1 demonstrates sub-tle midline anomalies not mentioned in the article, including hypogenesis or volume loss of the splenium (Figs 1A and E) and a partially fenestrated, persistent cavum septum pellucidum ( Fig 1D). 1 In normal brains, the callosal splenium is typically equal to or larger in caliber than the genu.…”
mentioning
confidence: 99%